Soft Robotics. - Monkman, Gareth J. (Bentham Science Publishers, 2022)
Soft robotics is a subfield of robotics that encompasses the design and fabrication of robots with soft and compliant materials. Soft robots represent components like human prosthetics or biomimicking systems. Soft robotics relies on technically astute designs based on the correct choice of materials to enable a level of dexterity not possible with rigid components alone. The basic prime movers (actuators) and perception (sensors) require control systems capable of accommodating imprecise feedback data and often unpredictable reaction times. Mobility in such robots is more akin to entomologica.
Description based upon print version of record.
Keywords: Robotics -- Human factors.; Robotique -- Facteurs humains.; Robotics -- Human factors